Organic reactions - Dauben, William G.; Bloomfield, Jordan J.; Caine, Drury (John Wiley & Sons, 1942)
Organic Reactions is a comprehensive series of volumes composed of chapters devoted to a single reaction, or a definite phase of a reaction. The material is treated from a preparative viewpoint, with emphasis on limitations, interfering influences, effects of structure, and the selection of experimental techniques. Numerous detailed procedures illustrate the significant modifications of each method. Includes tables that contain all possible examples of the reactions under consideration. This series provides the most comprehensive and highly focused treatment of important organic reactions currently available. All volumes of "Organic Reactions" (including this one) are collections of chapters each devoted to a single reaction or a definitive phase of a reaction, of wide applicability. The authors have had experience with the processes surveyed. The subjects are presented from the preparative viewpoint and particular attention is given to limitations, interfering influences, effects of structure and the selection of experimental techniques. Each chapter includes several detailed procedures illustrating the significant modifications of the method.